Investigation of the effect of cefazolin drug on swelling and mechanical and thermal properties of polyacrylamide-hydrogels using molecular dynamics approach - Ali Basem; Dheyaa J. Jasim; As'ad Alizadeh; Soheil Salahshour; Mohammad Hashemian (Results in Engineering)
Through molecular dynamics simulations, this study examined the interactions between water and cross-linked hydrogels, with a particular emphasis on the effect of cefazolin drug loading. The swelling percentage, ultimate strength, Young's modulus, heat flux, and thermal conductivity of polyacrylamide-based hydrogels were evaluated in relation to their respective drug concentrations (0 %, 3 %, 5 %, 15 %, and 30 %). The study results show that after 10 ns, the kinetic energy and total energy of atomic specimens stabilized at values of 12,532 and 12,488 kcal/mol, respectively. As the drug ratio increased from 0 to 15 %, the volume of polyacrylamide decreased from 342,722 to 302,583 Å³, with further increased from 15 to 30 % reducing the volume to 298,562 Å³ due to pore and interatomic space closure by the drug. As the drug ratio increased from 0 to 3 %, the ultimate strength of the simulated structure slightly decreased from 0.0333 to 0.0332 MPa, then increased to 0.0333 MPa at a 5 % drug ratio, and remained constant beyond that. The heat flux value decreased from 1583 to 1563 W/m2 with a drug ratio increase from 0 to 3 %, but then increased from 1563 to 1585 W/m2 as the drug ratio further increased to 30 %. Increasing the drug ratio had no effect on the thermal properties of simulated structure, and the thermal conductivity remained constant at 0.57 W/m·K with increasing cefazolin dosage.